MongoDB tools and services - Copeland, Rick; Safari eBooks ([Place of publication not identified] : Packt, 2017)
"The course takes you through real world examples that you can watch and use directly for your application. You will learn the ins and outs through the hacks covered in the course. This is your one stop course to boost your application performance for your audience. In this video course, we will explore the profiling and performance tools for MongoDB. We will make it even more accessible by moving to MongoDB cloud services, including analytics, automation, and even database-as-a-service. Finally, we will show different MongoDB cluster architectures affect application performance, scalability and reliability."--Resource description page.
Presenter, Rick Copeland.
Title from title screen (viewed August 28, 2017).
Date of publication taken from resource description page.
Keywords: Web applications -- Development; MongoDB; Cloud computing; Electronic books